Use of prebiotics and probiotics of bacterial and yeast origin for free-range broiler chickens - K Pelícia; AA Mendes; ESPB Saldanha; CC Pizzolante; SE Takahashi; J Moreira; RG Garcia; RR Quinteiro; ICLA Paz; CM Komiyama (Brazilian Journal of Poultry Science, 2004)
This study aimed to evaluate the effects of probiotics and prebiotics of bacterial and yeast origin on the performance, development of the digestive system, carcass yield and meat quality of free-range broiler chickens. Five hundred and sixty male chicks of the strain ISA S757-N were reared from one to 84 days old. The birds were distributed in four treatments according to a completely randomized block design: T1 = Control, T2 = Probiotics and Prebiotics of bacterial origin, T3 = Probiotics and prebiotics of yeast origin, T4 = Probiotics and prebiotics of bacterial origin + probiotics and prebiotics of yeast origin. There were four repetitions with 35 birds per repetition, and the birds had access to a pasture area after 35 days of age. Characteristics evaluated were performance, development of the digestive system, carcass and parts yield, abdominal fat, breast meat physical measurements (length, width and height) and meat quality parameters (pH from breast and leg meat, cooking loss and shearing force from breast meat). Lower mortality (p<0.05) and higher weight gain from 64 to 77 and 64 to 84 days of age were seen in birds supplemented with probiotics and prebiotics of bacterial origin compared to the non-supplemented birds (control). There were significant differences (p<0.05) among treatments for carcass yield. Birds supplemented with both probiotics and prebiotics of microbial and yeast origin (T4) showed higher carcass yield than control birds. Supplementation with probiotics and prebiotics of bacterial origin (T2) or the supplementation of these together with those of yeast origin (T4) reduced mortality and increased the carcass yield in free-range broiler chickens.